Cambridge reading: what's in the box? (big book) - Gillham, Bill; Jenkin-Pearce, Susie (Cambridge University Press UK, 1998)
"Cambridge Reading" Big Books provide texts that allow teachers to demonstrate early reading skills and strategies to large groups. This is a Big Book version of the popular "Beginning to Read" title "What's in the Box?"